BUTYLTIN RESIDUES IN SEDIMENTS FROM THE EASTERN GULF OF THAILAND - Praditsup, Nichaya; Wattayakorn, Gullaya (Marine Research in Indonesia, 2014)
Concentrations of monobutyltin (MBT), dibutyltin (DBT) and tributyltin (TBT) compounds were analyzedÂ in surface sediment samples collected from twelve stations along the Eastern Gulf of Thailand. The total butyltinÂ (â??BTs) concentrations ranged between <1 and 109.7 ng gÂ (dry weight). The overall concentration ranges foundÂ in the sediments were from <1 to 79.81 ng g-1Â for MBT, from <1 to 9.5 ng gÂ -1Â for DBT, and from <1 to 29.8 ng g-1 for TBT, on a dry weight basis. MBT generally prevailed in most of the samples, suggesting the occurrence of old inputs of butyltin compounds in the area. Butyltin compounds were also measured in Nassarius sp., where â??BTs concentrations were found to range between <1 and 238 ng g-1 (wet weight). The level of butyltin compounds in gastropod tissue samples tended to be related to that of the sediments and percentage of imposex incidence.